2015
DOI: 10.1097/pec.0000000000000322
|View full text |Cite
|
Sign up to set email alerts
|

Screening Adolescents for Sexually Transmitted Infections in the Pediatric Emergency Department

Abstract: Sexually transmitted infections were common in asymptomatic adolescents presenting to the PED. We identified 4 risk factors that were significantly associated with STIs. Our findings may facilitate identification of adolescents at highest risk for STIs, help prevent further transmission of infection, and decrease morbidity in this marginalized population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Although there are a few prior studies that have evaluated adolescent STI prevalence in EDs,(2022) this study offered screening to patients regardless of reported sexual activity and included an asymptomatic population solely. We chose these selection criteria to more precisely estimate the prevalence of STI in a cohort of patients who would be approached for screening if a universal STI screening protocol were instituted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are a few prior studies that have evaluated adolescent STI prevalence in EDs,(2022) this study offered screening to patients regardless of reported sexual activity and included an asymptomatic population solely. We chose these selection criteria to more precisely estimate the prevalence of STI in a cohort of patients who would be approached for screening if a universal STI screening protocol were instituted.…”
Section: Discussionmentioning
confidence: 99%
“…Our detected prevalence is similar to prevalence of N gonorrhoeae and C trachomatis infections found in other studies that did not select populations based on sexual activity, although these studies did not exclude symptomatic patients. (21, 22) However, rates of STI were associated with greater engagement in high risk sexual behavior and preferential use of the ED versus primary care, suggesting that a targeted screening strategy may offer the best balance between efficiency and benefit to patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Prior studies have shown a higher prevalence of GC/CT in patients of non-Hispanic black race/ethnicity, although it is not clear if this data reflects differences in exposure or more limited access to healthcare for screening and treatment. 1–2,5 Given the high prevalence of GC/CT in adolescents and the barriers to follow up, providers should strongly consider treatment for patients who have clinical indications for testing, regardless of race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Our detected prevalence is similar to prevalence of N gonorrhoeae and C trachomatis infections found in other studies that did not select populations based on sexual activity, although these studies did not exclude symptomatic patients. (21,22) However, rates of STI were associated with greater engagement in high risk sexual behavior and preferential use of the ED versus primary care, suggesting that a targeted screening strategy may offer the best balance between efficiency and benefit to patients. CDC, USPSTF, and AAP recommend annual screening.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a few prior studies that have evaluated adolescent STI prevalence in EDs, (20)(21)(22) this study offered screening to patients regardless of reported sexual activity and included an asymptomatic population solely. We chose these selection criteria to more precisely estimate the prevalence of STI in a cohort of patients who would be approached for screening if a universal STI screening protocol were instituted.…”
Section: Discussionmentioning
confidence: 99%